Fatty acids inhibit apical membrane chloride channels in airway epithelia. - Anderson, M P (1990)
Apical membrane Cl- channels control the rate of transepithelial Cl- secretion in airway epithelia. cAMP-dependent protein kinase and protein kinase C regulate Cl- channels by phosphorylation; in cystic fibrosis cells, phosphorylation-dependent activation of Cl- channels is defective. Another important signaling system involves arachidonic acid, which is released from cell membranes during receptor-mediated stimulation. Here we report that arachidonic acid reversibly inhibited apical membrane Cl- channels in cell-free patches of membrane. Arachidonic acid itself inhibited the channel and not a cyclooxygenase or lipoxygenase metabolite because (i) inhibitors of these enzymes did not block the response, (ii) fatty acids that are not substrates for the enzymes had the same effect as arachidonic acid, and (iii) metabolites of arachidonic acid did not inhibit the channel. Inhibition occurred only when fatty acids were added to the cytosolic surface of the membrane patch. Unsaturated fatty acids were more potent than saturated fatty acids. Arachidonic acid inhibited Cl- channels from both normal and cystic fibrosis cells. These results suggest that fatty acids directly inhibit apical membrane Cl- channels in airway epithelial cells.